Pengamalan Nilai Sipakatau, Sipakalibbi, Sipakainge, di Lingkungan Forum Komunikasi Mahasiswa Bone-Yogyakarta - Khusnul Khotimah (Thaqafiyyat : Jurnal Bahasa, Peradaban dan Informasi Islam, 2013)
One of the foundations of the establishment of family structure between individuals is determined by a person's attitude. The attitude is adopted by the Bugis ancestors in every sector of life in them are ready to take 'sipakatau, Sipakalebbi, sipakainge (grades 3 - S). But the era of modernization and this information becomes a threat to ethnic identity due to the lack of recognition and appreciation of their own cultural values , even closer to moral degradation. In the midst of these conditions, there is still some interest groups such as the culture -based regional organization that is driven by a group of intellectuals that organizations Bone Student Communication Forum (FKMB) in Yogyakarta. FKMB - Y seeks to preserve the cultural heritage especially Bugis culture through their social interactions on each activities. The purpose of this study is to explain the presence of members of FKMB - Y as one of the subjects of culture in cultural preservation Bugis community in Yogyakarta, know the life of the Bugis community in local knowledge, as well as provide an understanding of the concept of interaction - Y FKMB members in its activities. Results of studies have shown that the value sipakatau, Sipakalebbi, sipakainge not merely cultural values recognized by the community but also applied to his actions. Practice sipakatau value, Sipakalebbi, sipakainge been realized in social interaction student / student Bone Student Communication Forum in every activity, even into the principles of the organization in carrying out the mandate in writing.